Follicular Dynamics and Endocrine Profile during Normal Estrous Cycle and Early Pregnancy in Surti Buffaloes - Chaudhari, Dinesh V.; Panchal, Mahesh T.; Dhami, Arjan J.; Sarvaiya, Nitesh P.; Pathan, Mohsinkhan M.; Hadiya, Kamlesh K.; Patel, Jagdish A. (Indian Journal of Veterinary Sciences and Biotechnology, 2022)
The study was conducted on Surti buffaloes for follicular dynamics and endocrine profile during normal estrous cycle (n=6) and early pregnancy (n=6). In cyclic and early pregnant buffaloes, one-wave (33.33% vs. 50.00%) and two-waves (66.66% vs. 50.00%) follicular development was recorded, without three-wave pattern. In cyclic buffalo, the length of estrous cycle and duration of inter-ovulatory interval were little shorter in one wave cycles than in two wave cycles (22.50±0.50 and 23.25±0.25 days). The number of follicles differed non-significantly within and between cyclic and early pregnant buffaloes. The mean maximum diameter of dominant follicle of second wave was significantly larger in cyclic than early pregnant animals for two wave pattern (1.09±0.02 vs 0.73±0.02 cm). In cyclic buffaloes, the mean maximum CL size recorded was 1.21±0.02 and 1.52±0.05 cm (P<0.05) in one- and two-wave cycles, respectively, whereas in early pregnant buffaloes, the corresponding CL size was 1.50±0.04 and 1.55±0.07 cm without significant difference. Thus the mean maximum CL size of early pregnant buffaloes was significantly larger than the cyclic buffaloes with one-wave cycle (1.50±0.04 vs. 1.21±0.02 cm). In the normal cyclic animals, the CL size increased gradually up to day 8 (1.30±0.04 cm) and then remained stable up to day 18 (1.26±0.15 cm), followed by regression and display of next estrus between day 19 and 21, whereas in early pregnant animals the CL size gradually increased up to day 10 (1.48±0.07 cm) and then it was maintained till day 22 (1.46±0.04 cm) of monitoring. The mean diameter of largest follicle recorded was on the day of estrus (0.98±0.07 cm) with variable development of follicles during metestrus to diestrus phase with a new follicles developed during proestrus to estrus phase reaching maximum diameter of ovulatory size (0.99±0.09 cm) between days 19 and 21, whereas in early pregnant animals, the diameter of larger follicle (0.76±0.05 cm) was not recorded up to ovulatory size. The mean concentrations of serum progesterone were lowest during peri-estrus phase, increased through early-luteal phase to a maximum concentration during mid-luteal phase (4.50±0.88 to 4.67±0.95 ng/ml) and then gradually declined through late-luteal phase of diestrus in normal cyclic animals with inverse trend in estradiol profile. However, in early pregnant animals the progesterone levels gradually increased initially and then were maintained higher (6.17±0.32 to 8.13±0.55 ng/ml) with basal estradiol throughout the luteal phase. The serum progesterone/estradiol levels were in harmony with the ovarian dynamics in both cyclic and early pregnant buffaloes. The mean concentrations of serum FSH, LH and kisspeptin in normal cyclic and early pregnant animals did not vary statistically between periods within the status or between reproductive status of animals at any of the periods. The concentration of serum kisspeptin dropped significantly in advanced pregnancy as compared to first and second trimester.